Emotions, risk attitudes, and patience - Armando N. Meier (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Previous work has shown that preferences are not always stable across time, but surprisingly little is known about the reasons for this instability. I examine whether variation in people's emotions over time predicts changes in preferences. Using a large panel data set, I find that within-person changes in happiness, anger, and fear have substantial effects on risk attitudes and patience. Robustness checks indicate a limited role of alternative explanations. I further address potential endogeneity concerns by exploiting information about the death of a parent or child. This identification strategy confirms a large causal impact of emotions on preferences.
Keywords: D01; D90; D91; 330; emotions; risk attitudes; patience; risk preferences; time preferences